Case study of Guillain-Barré syndrome with acute flaccid paralysis - Sireesha, Vankodoth; Sahithya, Laxmi; Akshitha, Vaishali; Tadikonda, Rama Rao (International Journal of Contemporary Pediatrics, 2023)
Guillain-Barre syndrome (GBS) is a sudden and a complicated degenerative neurological disorder which can be acute or chronic in nature. Etiology remains unclear, but pathophysiology shows demyelination of spinal nerve roots characterised by symmetrical limb weakness and muscle stiffness. Death is rare. Early diagnosis and prompt treatment should occur in severe cases. Here we discuss a rare case of GBS as paraesthesia and acute flaccid paralysis. This case report focuses on a 9-year-old male patient presenting with c/o progressive muscle weakness and paraesthesia in the lower extremities. The clinical examination revealed bilateral lower limb weakness, absent deep tendon reflexes, and diminished vibration sense, acute flaccid paralysis. Diagnostic evaluations of CT scan of brain and spine and other preliminary tests confirmed the diagnosis of GBS by demonstrating characteristic findings of demyelinating polyneuropathy and elevated protein levels without pleocytosis, respectively. Prompt initiation of intravenous immunoglobulin therapy and supportive measures, such as physical therapy, were implemented. Over a four-week period, the patient showed progressive improvement in muscle strength, starting from the slight movement in fingers and toes. This case report underscores the importance of accurate diagnosis, and timely initiation of appropriate treatment strategies in managing GBS, highlighting the efficacy of intravenous immunoglobulin therapy as a first-line intervention for GBS patients.